Sufism a new history of Islamic mysticism - Knyš, Aleksandr Dmitrievič 1957- (Princeton University Press, 2017)
A pathbreaking history of Sufism, from the earliest centuries of Islam to the present. After centuries as the most important ascetic-mystical strand of Islam, Sufism saw a sharp decline in the twentieth century, only to experience a stunning revival in recent decades. In this comprehensive new history of Sufism from the earliest centuries of Islam to today, Alexander Knysh, a leading expert on the subject, reveals the tradition in all its richness. Knysh explores how Sufism has been viewed by both insiders and outsiders since its inception. He examines the key aspects of Sufism, from definitions and discourses to leadership, institutions, and practices. He devotes special attention to Sufi approaches to the Qur'an, drawing parallels with similar uses of scripture in Judaism and Christianity. He traces how Sufism grew from a set of simple moral-ethical precepts into a sophisticated tradition with professional Sufi masters (shaykhs) who became powerful players in Muslim public life but whose authority was challenged by those advocating the equality of all Muslims before God. Knysh also examines the roots of the ongoing conflict between the Sufis and their fundamentalist critics, the Salafis...a major fact of Muslim life today. Based on a wealth of primary and secondary sources, Sufism is an indispensable account of a vital aspect of Islam ...